The State of Mental, Emotional, and Behavioral Health of Children and Youth in the United States: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Over the past decade, providers, policy makers, and stakeholders across a range of disciplines have taken various approaches to addressing the rising incidence of mental, emotional, and behavioral (MEB) health concerns in children and adults. With the recent opioid crisis affecting young people and families across race, ethnicity, and socioeconomic level, and thus adding to the national concern, new efforts and interventions have emerged. However, an overarching system is lacking for the collection of data on these efforts and their efficacy. A strong system for evaluating programs and distributing information could create more opportunities to improve efforts and reduce inefficiencies across programs. Additionally, through engagement of an array of stakeholders from all sectors involved with youth and families, more possibilities for solutions can be realized. To bring together some of these relevant stakeholders and to highlight some of these potential solutions, the National Academies of Sciences, Engineering, and Medicine convened a workshop in October 2019. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Summertime Opportunities to Promote Healthy Child and Adolescent Development: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
What children and adolescents do and learn in the summertime can have profound effects on their health and well-being, educational attainment, and career prospects. To explore the influence of summertime activities on the lives of young people, the National Academies of Sciences, Engineering, and Medicine held a workshop in August 2016. The participants discussed a wide range of topics, including the value of play, healthy eating and physical activity, systemic approaches to skill development, program quality and measurement, and the interconnected ecosystem of activities that supports healthy development. The workshop highlighted the latest research on summer programming, as well as gaps in that research, and explored the key policy and practice issues for summertime opportunities to promote healthy child and adolescent development. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Implementing Juvenile Justice Reform: The Federal Role - National Research Council (The National Academies Press, 2014)
In the past decade, a number of state, local, and tribal jurisdictions have begun to take significant steps to overhaul their juvenile justice systems - for example, reducing the use of juvenile detention and out-of-home placement, bringing greater attention to racial and ethnic disparities, looking for ways to engage affected families in the process, and raising the age at which juvenile court jurisdiction ends. These changes are the result of heightening awareness of the ineffectiveness of punitive practices and accumulating knowledge about adolescent development. Momentum for reform is growing. However, many more state, local, and tribal jurisdictions need assistance, and practitioners in the juvenile justice field are looking for guidance from the federal government, particularly from the Office of Juvenile Justice and Delinquency Prevention (OJJDP) in the Department of Justice. Implementing Juvenile Justice Reform identifies and prioritizes strategies and policies to effectively facilitate reform of the juvenile justice system and develop an implementation plan for OJJDP. Based on the 2013 report Reforming Juvenile Justice, this report is designed to provide specific guidance to OJJDP regarding the steps that it should take, both internally and externally, to facilitate juvenile justice reform grounded in knowledge about adolescent development. The report identifies seven hallmarks of a developmental approach to juvenile justice to guide system reform: accountability without criminalization, alternatives to justice system involvement, individualized response based on needs and risks, confinement only when necessary for public safety, genuine commitment to fairness, sensitivity to disparate treatment, and family engagement. Implementing Juvenile Justice Reform outlines how these hallmarks should be incorporated into policies and practices within OJJDP, as well as in actions extended to state, local, and tribal jurisdictions to achieve the goals of the juvenile justice system through a developmentally informed approach. This report sets forth a detailed and prioritized strategic plan for the federal government to support and facilitate developmentally oriented juvenile justice reform. The pivotal component of the plan is to strengthen the role, capacity, and commitment of OJJDP, the lead federal agency in the field. By carrying out the recommendations of Implementing Juvenile Justice Reform, the federal government will both reaffirm and advance the promise of the Juvenile Justice and Delinquency Prevention Act.
Keywords: Behavioral and Social Sciences

Juvenile Crime, Juvenile Justice - National Research Council; Institute of Medicine (The National Academies Press, 2001)
Even though youth crime rates have fallen since the mid-1990s, public fear and political rhetoric over the issue have heightened. The Columbine shootings and other sensational incidents add to the furor. Often overlooked are the underlying problems of child poverty, social disadvantage, and the pitfalls inherent to adolescent decisionmaking that contribute to youth crime. From a policy standpoint, adolescent offenders are caught in the crossfire between nurturance of youth and punishment of criminals, between rehabilitation and "get tough" pronouncements. In the midst of this emotional debate, the National Research Council's Panel on Juvenile Crime steps forward with an authoritative review of the best available data and analysis. Juvenile Crime, Juvenile Justice presents recommendations for addressing the many aspects of America's youth crime problem. This timely release discusses patterns and trends in crimes by children and adolescents—trends revealed by arrest data, victim reports, and other sources; youth crime within general crime; and race and sex disparities. The book explores desistance—the probability that delinquency or criminal activities decrease with age—and evaluates different approaches to predicting future crime rates. Why do young people turn to delinquency? Juvenile Crime, Juvenile Justice presents what we know and what we urgently need to find out about contributing factors, ranging from prenatal care, differences in temperament, and family influences to the role of peer relationships, the impact of the school policies toward delinquency, and the broader influences of the neighborhood and community. Equally important, this book examines a range of solutions: Prevention and intervention efforts directed to individuals, peer groups, and families, as well as day care-, school- and community-based initiatives. Intervention within the juvenile justice system. Role of the police. Processing and detention of youth offenders. Transferring youths to the adult judicial system. Residential placement of juveniles. The book includes background on the American juvenile court system, useful comparisons with the juvenile justice systems of other nations, and other important information for assessing this problem.
Keywords: Behavioral and Social Sciences

Mental Health, Substance Use, and Wellbeing in Higher Education: Supporting the Whole Student - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Student wellbeing is foundational to academic success. One recent survey of postsecondary educators found that nearly 80 percent believed emotional wellbeing is a "very" or "extremely" important factor in student success. Studies have found the dropout rates for students with a diagnosed mental health problem range from 43 percent to as high as 86 percent. While dealing with stress is a normal part of life, for some students, stress can adversely affect their physical, emotional, and psychological health, particularly given that adolescence and early adulthood are when most mental illnesses are first manifested. In addition to students who may develop mental health challenges during their time in postsecondary education, many students arrive on campus with a mental health problem or having experienced significant trauma in their lives, which can also negatively affect physical, emotional, and psychological wellbeing. The nation's institutions of higher education are seeing increasing levels of mental illness, substance use and other forms of emotional distress among their students. Some of the problematic trends have been ongoing for decades. Some have been exacerbated by the COVID-19 pandemic and resulting economic consequences. Some are the result of long-festering systemic racism in almost every sphere of American life that are becoming more widely acknowledged throughout society and must, at last, be addressed. Mental Health, Substance Use, and Wellbeing in Higher Education lays out a variety of possible strategies and approaches to meet increasing demand for mental health and substance use services, based on the available evidence on the nature of the issues and what works in various situations. The recommendations of this report will support the delivery of mental health and wellness services by the nation's institutions of higher education.
Keywords: Health and Medicine; Education

Strengthening the Military Family Readiness System for a Changing American Society - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. military has been continuously engaged in foreign conflicts for over two decades. The strains that these deployments, the associated increases in operational tempo, and the general challenges of military life affect not only service members but also the people who depend on them and who support them as they support the nation – their families. Family members provide support to service members while they serve or when they have difficulties; family problems can interfere with the ability of service members to deploy or remain in theater; and family members are central influences on whether members continue to serve. In addition, rising family diversity and complexity will likely increase the difficulty of creating military policies, programs and practices that adequately support families in the performance of military duties. Strengthening the Military Family Readiness System for a Changing American Society examines the challenges and opportunities facing military families and what is known about effective strategies for supporting and protecting military children and families, as well as lessons to be learned from these experiences. This report offers recommendations regarding what is needed to strengthen the support system for military families.
Keywords: Behavioral and Social Sciences

Public Health Consequences of E-Cigarettes - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Millions of Americans use e-cigarettes. Despite their popularity, little is known about their health effects. Some suggest that e-cigarettes likely confer lower risk compared to combustible tobacco cigarettes, because they do not expose users to toxicants produced through combustion. Proponents of e-cigarette use also tout the potential benefits of e-cigarettes as devices that could help combustible tobacco cigarette smokers to quit and thereby reduce tobacco-related health risks. Others are concerned about the exposure to potentially toxic substances contained in e-cigarette emissions, especially in individuals who have never used tobacco products such as youth and young adults. Given their relatively recent introduction, there has been little time for a scientific body of evidence to develop on the health effects of e-cigarettes. Public Health Consequences of E-Cigarettes reviews and critically assesses the state of the emerging evidence about e-cigarettes and health. This report makes recommendations for the improvement of this research and highlights gaps that are a priority for future research.
Keywords: Health and Medicine

Investing in the Health and Well-Being of Young Adults - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Young adulthood - ages approximately 18 to 26 - is a critical period of development with long-lasting implications for a person's economic security, health and well-being. Young adults are key contributors to the nation's workforce and military services and, since many are parents, to the healthy development of the next generation. Although 'millennials' have received attention in the popular media in recent years, young adults are too rarely treated as a distinct population in policy, programs, and research. Instead, they are often grouped with adolescents or, more often, with all adults. Currently, the nation is experiencing economic restructuring, widening inequality, a rapidly rising ratio of older adults, and an increasingly diverse population. The possible transformative effects of these features make focus on young adults especially important. A systematic approach to understanding and responding to the unique circumstances and needs of today's young adults can help to pave the way to a more productive and equitable tomorrow for young adults in particular and our society at large. Investing in The Health and Well-Being of Young Adults describes what is meant by the term young adulthood, who young adults are, what they are doing, and what they need. This study recommends actions that nonprofit programs and federal, state, and local agencies can take to help young adults make a successful transition from adolescence to adulthood. According to this report, young adults should be considered as a separate group from adolescents and older adults. Investing in The Health and Well-Being of Young Adults makes the case that increased efforts to improve high school and college graduate rates and education and workforce development systems that are more closely tied to high-demand economic sectors will help this age group achieve greater opportunity and success. The report also discusses the health status of young adults and makes recommendations to develop evidence-based practices for young adults for medical and behavioral health, including preventions. What happens during the young adult years has profound implications for the rest of the life course, and the stability and progress of society at large depends on how any cohort of young adults fares as a whole. Investing in The Health and Well-Being of Young Adults will provide a roadmap to improving outcomes for this age group as they transition from adolescence to adulthood.
Keywords: Health and Medicine; Behavioral and Social Sciences

The Impact of Juvenile Justice System Involvement on the Health and Well-Being of Youth, Families, and Communities of Color: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Involvement with the juvenile justice system can impact young people's physical and mental health and well-being throughout their lives, as well as the health and well-being of their families and communities. Youth of color are more likely to become involved with the juvenile justice system, and suffer worse outcomes in sentencing, during incarceration, and after release. The National Academies of Sciences, Engineering, and Medicine's Roundtable on the Promotion of Health Equity convened a workshop to discuss the impact that juvenile justice system involvement has on the health and well-being of adolescents, families, and communities of color; examine policies that are successful in improving outcomes; and explore what needs to be done to improve all aspects of encounters with the juvenile justice system. The workshop suggested pursuing alternatives to traditional juvenile justice systems that would allow adolescents to stay in their communities rather than in detention, responding to behavioral problems in youth with interventions that promote health and positive development rather than punishment, and tailoring interventions and programming to participants' cultural background and gender identity. This report summarizes the proceedings of the workshop.
Keywords: Health and Medicine

Improving the Health, Safety, and Well-Being of Young Adults: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Young adults are at a significant and pivotal time of life. They may seek higher education, launch their work lives, develop personal relationships and healthy habits, and pursue other endeavors that help set them on healthy and productive pathways. However, the transition to adulthood also can be a time of increased vulnerability and risk. Young adults may be unemployed and homeless, lack access to health care, suffer from mental health issues or other chronic health conditions, or engage in binge drinking, illicit drug use, or driving under the influence. Young adults are moving out of the services and systems that supported them as children and adolescents, but adult services and systems—for example, the adult health care system, the labor market, and the justice system—may not be well suited to supporting their needs. Improving the Health, Safety, and Well-Being of Young Adults is the summary of a workshop hosted by the Board on Children, Youth, and Families of the Institute of Medicine (IOM) and the National Research Council (NRC) in May, 2013. More than 250 researchers, practitioners, policy makers, and young adults presented and discussed research on the development, health, safety, and well-being of young adults. This report focuses on the developmental characteristics and attributes of this age group and its placement in the life course; how well young adults function across relevant sectors, including, for example, health and mental health, education, labor, justice, military, and foster care; and how the various sectors that intersect with young adults influence their health and well-being. Improving the Health, Safety, and Well-Being of Young Adults provides an overview of existing research and identifies research gaps and issues that deserve more intensive study. It also is meant to start a conversation aimed at a larger IOM/NRC effort to guide research, practices, and policies affecting young adults.
Keywords: Health and Medicine

Shaping Summertime Experiences: Opportunities to Promote Healthy Development and Well-Being for Children and Youth - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
For children and youth, summertime presents a unique break from the traditional structure, resources, and support systems that exist during the school year. For some students, this time involves opportunities to engage in fun and enriching activities and programs, while others face additional challenges as they lose a variety of supports, including healthy meals, medical care, supervision, and structured programs that enhance development. Children that are limited by their social, economic, or physical environments during the summer months are at higher risk for worse academic, health, social and emotional, and safety outcomes. In contrast, structured summertime activities and programs support basic developmental needs and positive outcomes for children and youth who can access and afford these programs. These discrepancies in summertime experiences exacerbate pre-existing academic inequities. While further research is needed regarding the impact of summertime on developmental domains outside of the academic setting, extensive literature exists regarding the impact of summertime on academic development trajectories. However, this knowledge is not sufficiently applied to policy and practice, and it is important to address these inequalities. Shaping Summertime Experiences examines the impact of summertime experiences on the developmental trajectories of school-age children and youth across four areas of well-being, including academic learning, social and emotional development, physical and mental health, and health-promoting and safety behaviors. It also reviews the state of science and available literature regarding the impact of summertime experiences. In addition, this report provides recommendations to improve the experiences of children over the summertime regarding planning, access and equity, and opportunities for further research and data collection.
Keywords: Behavioral and Social Sciences

Fostering Healthy Mental, Emotional, and Behavioral Development in Children and Youth: A National Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Healthy mental, emotional, and behavioral (MEB) development is a critical foundation for a productive adulthood. Much is known about strategies to support families and communities in strengthening the MEB development of children and youth, by promoting healthy development and also by preventing and mitigating disorder, so that young people reach adulthood ready to thrive and contribute to society. Over the last decade, a growing body of research has significantly strengthened understanding of healthy MEB development and the factors that influence it, as well as how it can be fostered. Yet, the United States has not taken full advantage of this growing knowledge base. Ten years later, the nation still is not effectively mitigating risks for poor MEB health outcomes; these risks remain prevalent, and available data show no significant reductions in their prevalence. Fostering Healthy Mental, Emotional, and Behavioral Development in Children and Youth: A National Agenda examines the gap between current research and achievable national goals for the next ten years. This report identifies the complexities of childhood influences and highlights the need for a tailored approach when implementing new policies and practices. This report provides a framework for a cohesive, multidisciplinary national approach to improving MEB health.
Keywords: Behavioral and Social Sciences

Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer is the summary of a workshop convened by the Institute of Medicine's National Cancer Policy Forum in July 2013 to facilitate discussion about gaps and challenges in caring for adolescent and young adult cancer patients and potential strategies and actions to improve the quality of their care. The workshop featured invited presentations from clinicians and other advocates working to improve the care and outcomes for the adolescent and young adult population with cancer. Cancer is the leading disease-related cause of death in adolescents and young adults. Each year nearly 70,000 people between the ages of 15 and 39 are diagnosed with cancer, approximately 8 times more than children under age 15. This population faces a variety of unique short- and long-term health and psychosocial issues, such as difficulty reentering school, the workforce, or the dating scene; problems with infertility; cardiac, pulmonary, or other treatment repercussions; and secondary malignancies. Survivors are also at increased risk for psychiatric conditions such as anxiety, depression, substance abuse, and suicide and may have difficulty acquiring health insurance and paying for needed care. Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer discusses a variety of topics important to adolescent and young adult patients with cancer, including the ways in which cancers affecting this group differ from cancers in other age groups and what that implies about the best treatments for these cancer patients. This report identifies gaps and challenges in providing optimal care to adolescent and young adult patients with cancer and to discuss potential strategies and actions to address them.
Keywords: Health and Medicine

Reforming Juvenile Justice: A Developmental Approach - National Research Council (The National Academies Press, 2013)
Adolescence is a distinct, yet transient, period of development between childhood and adulthood characterized by increased experimentation and risk-taking, a tendency to discount long-term consequences, and heightened sensitivity to peers and other social influences. A key function of adolescence is developing an integrated sense of self, including individualization, separation from parents, and personal identity. Experimentation and novelty-seeking behavior, such as alcohol and drug use, unsafe sex, and reckless driving, are thought to serve a number of adaptive functions despite their risks. Research indicates that for most youth, the period of risky experimentation does not extend beyond adolescence, ceasing as identity becomes settled with maturity. Much adolescent involvement in criminal activity is part of the normal developmental process of identity formation and most adolescents will mature out of these tendencies. Evidence of significant changes in brain structure and function during adolescence strongly suggests that these cognitive tendencies characteristic of adolescents are associated with biological immaturity of the brain and with an imbalance among developing brain systems. This imbalance model implies dual systems: one involved in cognitive and behavioral control and one involved in socio-emotional processes. Accordingly adolescents lack mature capacity for self-regulations because the brain system that influences pleasure-seeking and emotional reactivity develops more rapidly than the brain system that supports self-control. This knowledge of adolescent development has underscored important differences between adults and adolescents with direct bearing on the design and operation of the justice system, raising doubts about the core assumptions driving the criminalization of juvenile justice policy in the late decades of the 20th century. It was in this context that the Office of Juvenile Justice and Delinquency Prevention (OJJDP) asked the National Research Council to convene a committee to conduct a study of juvenile justice reform. The goal of Reforming Juvenile Justice: A Developmental Approach was to review recent advances in behavioral and neuroscience research and draw out the implications of this knowledge for juvenile justice reform, to assess the new generation of reform activities occurring in the United States, and to assess the performance of OJJDP in carrying out its statutory mission as well as its potential role in supporting scientifically based reform efforts.
Keywords: Behavioral and Social Sciences

Reducing Inequalities Between Lesbian, Gay, Bisexual, Transgender, and Queer Adolescents and Cisgender, Heterosexual Adolescents: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
To better understand the inequalities facing lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth and the promising interventions being used to address these inequalities, the National Academies of Sciences, Engineering, and Medicine's Board on Children, Youth, and Families hosted a virtual public workshop titled Reducing Inequalities Between LGBTQ Adolescents and Cisgender, Heterosexual Adolescents, which convened on August 25–27, 2021. The workshop was developed by a planning committee composed of experts from the fields of sociology, medicine, public health, psychology, social work, policy, and direct-service provision. This Proceedings of a Workshop summarizes the presentations and discussions from that workshop.
Keywords: Behavioral and Social Sciences

Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Adolescence is a critical growth period in which youth develop essential skills that prepare them for adulthood. Prevention and intervention programs are designed to meet the needs of adolescents who require additional support and promote healthy behaviors and outcomes. To ensure the success of these efforts, it is essential that they include reliably identifiable techniques, strategies, or practices that have been proven effective. Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century identifies key program factors that can improve health outcomes related to adolescent behavior and provides evidence-based recommendations toward effective implementation of federal programming initiatives. This study explores normative adolescent development, the current landscape of adolescent risk behavior, core components of effective programs focused on optimal health, and recommendations for research, programs, and policies.
Keywords: Behavioral and Social Sciences; Health and Medicine

Applying Lessons of Optimal Adolescent Health to Improve Behavioral Outcomes for Youth: Public Information-Gathering Session: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The Committee on Applying Lessons of Optimal Adolescent Health to Improve Behavioral Outcomes for Youth is conducting a study to identify key components of youth-serving programs that have proved successful in improving health outcomes related to adolescent behavior. As a part of this work, the committee held a public information-gathering session on April 17, 2019. The day-long session consisted of five panels: (1) health education decision making in public education systems, (2) effective measurement and evaluation of adolescent behaviors and behavioral interventions, (3) effective elements of programs focused on adolescent behavior, (4) evaluations of the Teen Pregnancy Prevention (TPP) Program and sex education programs, and (5) a discussion with youth. This public session represents just one of the ways in which the committee is gathering information for their report. This publication summarizes the presentations and discussions from the session.
Keywords: Behavioral and Social Sciences

Family-Focused Interventions to Prevent Substance Use Disorders in Adolescence: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Adolescence is a crucial period of life for the prevention of substance use disorders. Research has shown that early intervention can significantly reduce rates of substance use disorder in adulthood. To learn more about effective family-focused interventions in primary care settings for preventing substance use disorder, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on May 5-6, 2022. The proceedings from that workshop explores existing efforts to incorporate family-focused interventions into state health care policies. It also examines barriers to implementing such interventions as well as lessons learned from successful efforts to scale up these interventions.
Keywords: Behavioral and Social Sciences

Responding to the Current Youth Mental Health Crisis and Preventing the Next One: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Across the country, mental health concerns are affecting children and youth in every community. Mental health providers are witnessing increased numbers of patients and increased severity in reported concerns. In the midst of this crisis, communities are exploring strategies for addressing children and youth's mental health, including increased investment in prevention. Given this current crisis, and the unprecedented response and potentially increased funding, there are opportunities to learn how to better incorporate prevention and promotion strategies into systems and programs for children and youth support. To explore these opportunities, the National Academies' Forum for Children's Well-Being held a 3-day workshop in May 2022. This Proceedings of a Workshop-in Brief provides a high-level summary of the topics addressed in the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Flourishing in Adolescence: A Virtual Workshop: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Adolescence is a dynamic time for both brain development and social pressures, making it a critical period to understand mental, emotional, and behavioral health, yet it is often overlooked in terms of policies and service interventions, which makes many young people feel unheard when communicating their own challenges. To explore best practices in providing and supporting adolescent health services and key messaging and communication strategies related to the mental, emotional, and behavioral health of adolescents, the National Academies of Sciences, Engineering, and Medicine's Forum for Children's Well-Being held a workshop on May 5, 2020. The workshop featured a panel of youth representatives who shared their own experiences related to mental, emotional, and behavioral health. This publication summarizes the presentation and discussion of the workshop.
Keywords: Behavioral and Social Sciences